(untitled) (Plant Tissue Culture and Biotechnology, 2010)
Leaf explants of Plumbago rosea L. an important medicinal plant inoculated on MS supplemented with 6.66 mM BAP and 2.69 mM NAA produced numerous (105 ± 0.3) shootlets with an average length of 3.1 ± 0.0 cm. Small shootlets were transferred to shoot elongation medium supplemented with 1.11 mM BAP plus 1.44 mM GA3. The elongated shootlets transferred to half strength MS basal medium without any plant growth regulator produced 4.3 ± 0.2 rootlets per plants with average root length of 4.0 ± 0.0 cm after 25 days of culture. Rooted plantlets were transferred for hardening showed 80 - 90 per cent of plantlets success-fully established in the field. Potentially more than 50,000 plantlets could be produced within five subcultures from without callus phase obtained from leaf explant. Maximum root differentiation from leaf explants was obtained on MS supplemented with 5.38 mM IBA. The roots developed by the above method is an alternative for the controlled production of secondary metabolites. Key words: In vitro culture, leaf explants, mass propagation, Plumbago rosea D.O.I. 10.3329/ptcb.v19i1.4989 Plant Tissue Cult. & Biotech. 19(1): 79-87, 2009 (June)